Mast cells: A unique source of renin - Silver, Randi B. (National Academy of Sciences, 2004)
In addition to the traditional renin–angiotensin system, a great deal of evidence favors the existence of numerous independent tissue-specific renin–angiotensin systems. We report that mast cells are an additional source of renin and constitute a unique extrarenal renin–angiotensin system. We use renin-specific antibodies to demonstrate that cardiac mast cells contain renin. Extending this observation to the human mast cell line HMC-1, we show that these mast cells also express renin. The HMC-1 renin RT-PCR product is 100% homologous to Homo sapiens renin. HMC-1 cells also contain renin protein, as demonstrated both by immunoblot and immunocytochemical analyses. Renin released from HMC-1 cells is active; furthermore, HMC-1 cells are able to synthesize renin. It is known that, in the heart, mast cells are found in the interstitium in close proximity to nerves and myocytes, which both express angiotensin II receptors. Inasmuch as myocardial interstitium contains angiotensinogen and angiotensin-converting enzyme, and because we were able to detect renin only in mast cells, we postulate that the release of renin from cardiac mast cells is the pivotal event triggering local formation of angiotensin II. Because of the ubiquity of mast cells, our results represent a unique paradigm for understanding local renin–angiotensin systems, not just in the heart, but in all tissues. Our findings provide a rationale for targeting mast cells in conjunction with renin–angiotensin system inhibitors in the management of angiotensin II-related dysfunctions.